Does Polychronicity Undermine Procrastination Behavior Through ICTs? Insights From Multi-Level Modeling - Xiaolong, Tao; Gull, Nida; Akram, Zubair; Asghar, Muhammad; Jianmin, Zhang (Frontiers in Psychology, 2021)
Information and communication technologies (ICTs) are widely used in developing nations as a dynamic solution for socio-economic development. Pakistan has seen a rapid increase in the use of ICTs during the previous decade. The purpose of this study is to examine how polychronicity affects procrastination behavior when it is influenced by ICTs. According to this study, individuals are described as a dynamic and destructive kind of self-regulation failure in ICTs. Procrastination is a behaviour that prevents emerging economies from growing from developing countries. We researched the group-level polychronicity influence of the individual behavior and the mechanism of procrastination from a team-level perspective of worker behaviour. This study data collected 231 workers from 76 groups working in Pakistan's ICTs. The results revealed that the group polychronicity and the behaviour of group members were positively linked by taking the work overload as a mediator. Moreover, group cohesiveness moderates the role between polychronicity and work overload diminishing the mediation procession between-group polychronicity and individual procrastination. The practical organizational importance of the study is to understand and causes of procrastination, how to decrease this obstacle to a fairer workplace. It also helps decide the professional route most suited to personality characteristics.